An Educational Video Game Based on Basic Principle of Biology - Noor Ain, Rosly; Amirul Azuani, Romlee; Lim, Zhi Yue (INTI International University, 2019)
Video games have been extremely attractive to gamers of all ages, especially the young ones. They spend much time playing such games for pleasure and entertainment. Thus, this paper aims to gamify education by incorporating 3D video games elements into science subjects. Science subjects such as Biology have always been visualize by students to be difficult because there are a lot of concept and processes to be memorized. This leads to lack of interest in learning Biology Science subject among students in Malaysia. This application focuses on microorganism topic. Apart from that, the elements of effective educational video game design in terms of motivation, narrative of context, goals and rules and interactivity to further engage student in their learning process will be discussed. The benefit of student-generated activities using 3D video games and Biology subject for secondary school explained further in this paper. Playing video games, as a lifestyle habit, by respondents shows an association with positive attitude. In other words, those who play video games themselves are more likely to have favorable attitudes toward using those games for education.